Effect of Xenon on the Structural Phase State of the Surface Layer of Cemented Carbide under Pulsed Electron-Beam Irradiation - Ovcharenko V. E. Vladimir Efimovich; Ivanov Yu. F. Yuriy Fedorovich; Mokhovikov A. A. Aleksey Aleksandrovich; Yu Baohai; Xiaolong Cai; Lisheng Zhong; Yunhua Xu (2015, 2015)
Title screen